Ownership structure, corporate risk disclosure and firm value: a study on Malaysian public listed firms / Siti Aisyah Kamaruzaman - Kamaruzaman, Siti Aisyah (2015)
This study examines the nature and extent of risk reporting practices among Malaysian public listed firms. This study analyses the regulated and non-regulated risk-related information and examines the relationship between the level of risk disclosure and firm value. This study also examines the relationship between ownership structure and corporate risk disclosure. Specifically, this study focuses on three types of ownership namely, managerial ownership, institutional ownership and family ownership. This study used content analysis on 200 top listed firms in Bursa Malaysia and risk-related information was coded based on the number of sentences representing the pre-determined keywords. The result of this study shows a negative relationship between regulated risk disclosure and firm value. One of the reasons could be attributed by the cost of reporting outweighs the benefits in preparing the information. In addition, the regulated risk disclosure is positively associated with institutional ownership. In terms of non-regulated risk disclosure, the result shows that there is a negative relationship between managerial ownership and family ownership. This can be explained by the family members in family-owned firms, or the board o directors in the manager-owned firms may already have access to the privileged information. The results in this study provide some understanding for the supervisory bodies in evaluating the level of compliance related to risk reporting practices. The findings in this study also assist investors to consider ownership structure of the prospect firm as one of the criteria in decision-making.